PENGARUH KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN - Hasriani Hasriani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
Performance is the responsibility of each individual to the job, helping to define performance expectations, seeking a framework for supervisors and workers communicate with each other. The goal is to adjust the performance of individual performance expectations with organizational goals. Correspondence between efforts to achieve individual goals with organizational goals will be able to achieve good performance